X-linked TLR7 gene polymorphisms are associated with diverse immunological conditions but not with discoid lupus erythematosus in Polish patients - Skonieczna, Katarzyna; Woźniacka, Anna; Czajkowski, Rafał; Styczyński, Jan; Krenska, Anna; Robak, Ewa; Gawrych, Mariusz; Kaszewski, Sebastian; Wysocki, Mariusz; Grzybowski, Tomasz (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2018)
Introduction : Toll-like receptor 7 (TLR7) is an important molecule involved in the development of autoimmunity and the response to different pathogens. Several polymorphisms within the TLR7 gene were previously found to be associated with systemic lupus erythematosus (SLE). However, none of those studies investigated the TLR7 promoter flanking variants rs1634318 and rs1616583. TLR7 gene diversity has not been analyzed with respect to discoid lupus erythematosus (DLE) development, while its role in the human immunological response to fungal infection is not fully known. Aim : To clarify the potential involvement of two novel single-nucleotide polymorphisms (SNPs) located in the TLR7 gene (rs1634318 and rs1616583) in a variety of immune-related conditions, we studied the variability of these loci in patients from a Polish population with SLE and DLE, as well as in immunocompromised patients who were affected by invasive aspergillosis (IA) and those who were not affected. Material and methods : Real-time polymerase chain reaction was used to genotype SNPs. Statistically significant differences between case and control groups for both allele and genotype frequencies were assessed using the 2 test with Yates’ correction or two-tailed Fisher’s exact test. The results were Bonferroni-corrected for multiple comparisons and odds ratios were calculated. Results : Two polymorphisms located in TLR7 might be associated with the development of SLE but not DLE within the Polish population. Moreover, variation of the two investigated SNPs was found to be associated with IA in immunocompromised Polish patients. Conclusions : In Polish patients, TLR7 promoter flanking gene polymorphisms might be associated with IA and SLE but not DLE.